Motif Hubungan Kerjasama Antara KRG (Kurdish Regional Government) Irak Dengan Pemerintah Turki (2013-2016) - Maryam Jamilah (Department of International Relations, Universitas Andalas, 2018)
This research aims to analyze motives behind cooperation between KRG (Kurdish Regional Government) and Turkey government by using neorealism perspective of International relations. On neorealism, state as rational actor will try to maintain their existance or to survive in international system of anarchy. Significhant change of KRG and Turkey government relation, which was in bad term bercause of Turkey rejection of KRG as political entity but then they cooperate after AKP (adalet ve Kalkinma Partisi) or Justice and Development Party won the Turkey election in 2002. That is the main focus of this research, the purpose is to formulize motives behind coopertion between those two entities.The findings of this research is there are two main motives of cooperation between them: first, good relation between them is in order to achieve their own self interest, second, mutual benefit that they get from cooperation is more bigger.Keywords: motives, cooperation, KRG, Turkey, neorelism, interest